Duets defend mates in a suboscine passerine, the warbling antbird (Hypocnemis cantator) - Seddon, N; Tobias, J (2006)
Despite the widespread occurrence of avian duets, their adaptive significance is poorly understood. It is generally assumed that they function in the joint defense of territories, but no study has successfully distinguished between this hypothesis, which invokes cooperation between the sexes, and mate defense, which invokes conflict. Further, most duetting studies have focused on oscine passerines, the songs of which are learnt and relatively complex. We therefore tested the mate defense hypothesis in the warbling antbird (Hypocnemis cantator), an Amazonian suboscine that produces simple sex-specific songs and duets. Acoustic analysis of songs showed (1) that solos were often produced by males, but rarely by females; (2) that duets consisted of a male song and a female reply; and (3) that, although female song was invariable, a swift reply resulted in males producing shorter songs with fewer notes. These results suggest that duetting, and the structure of duets, is chiefly a product of female behavior, a scenario more suggestive of conflict than cooperation. To investigate this idea we carried out playback experiments, which showed that (4) the response to solo songs was sex specific (i.e., male solos elicited a strong response from paired males, and female solos elicited a strong response from paired females); (5) males and females responded to same-sex solos more strongly than to duets; and that (6) females answered their partner's songs more often, and more rapidly, in response to female solos than male solos or duets. Although it can be argued that sex-specific responses to solo song result from intrasexual territorial defense, we cannot use the same reasoning to explain (5) or (6). Instead, these observations imply that solitary intruders were more threatening than paired intruders, and thus that the perceived threat was to the partnership rather than the territory. Taken together, findings (1) to (6) suggest that females adjust their vocal behavior in relation to the level of perceived threat to the partnership, and duet with males in order to repel same-sex rivals. This study therefore strengthens support for the mate defense hypothesis, and suggests that conflict - rather than cooperation - may have played a major role in the evolution and maintenance of avian duets. © The Author 2005. Published by Oxford University Press on behalf of the International Society for Behavioral Ecology. All rights reserved.